Optimum Detection of Ultrasonic Echoes Applied to the Analysis of the First Layer of a Restored Dome. (14th August 2007) - Vergara Vergara, Luis Luis; Bosch Bosch, Ignacio Ignacio; Gosálbez Gosálbez, Jorge Jorge; Salazar Salazar, Addisson Addisson
Abstract : Optimum detection is applied to ultrasonic signals corrupted with significant levels of grain noise. The aim is to enhance the echoes produced by the interface between the first and second layers of a dome to obtain interface traces in echo pulse B-scan mode. This is useful information for the restorer before restoration of the dome paintings. Three optimum detectors are considered: matched filter, signal gating, and prewhitened signal gating. Assumed models and practical limitations of the three optimum detectors are considered. The results obtained in the dome analysis show that prewhitened signal gating outperforms the other two optimum detectors.